Three-dimensional non-close-packed structures of oppositely charged colloids driven by pH oscillation - Lei, Qun-li (2019)
The implementation of non-close-packed structures in colloids is challenging. Using Brownian dynamics simulations, we study the nonequilibrium self-assembly in suspensions of oppositely charged particles, whose charge magnitude is responsive to the pH of the solution. Under the fast pH-oscillating condition, various non-close-packed (e.g., graphitelike and diamondlike) structures are obtained. Here, changing the amplitude of the pH oscillation is an effective way to fabricate colloidal dynamic structures. To clarify the underlying mechanism of the dynamic self-assembly, the analysis of effective potential is adopted. A dimensionless parameter, the ratio of effective repulsion and attraction, is introduced to reflect the subtle interactions in the system. We find that the imbalance between repulsion and attraction is the cause of structural diversity. Madelung energy is used to study the stability of these structures. Our results provide a new way to fabricate non-close-packed structures in colloids, which has potential applications in the synthesis of photonic crystals.